2015
DOI: 10.1039/c5lc00090d
|View full text |Cite
|
Sign up to set email alerts
|

Resonant dielectrophoresis and electrohydrodynamics for high-sensitivity impedance detection of whole-cell bacteria

Abstract: We present the co-integration of CMOS-compatible Al/Al2O3 interdigitated microelectrodes (IDEs) with an electrokinetic-driven macroelectrode for sensitive detection of whole-cell bacteria in a microfluidic channel. Two frequency ranges applied to the macroelectrode were identified to notably increase the bacterial coverage of the impedimetric sensor per unit time. Around 10 kHz, the bacterial cells were directed towards the IDE center thanks to AC electroosmosis (AC-EO) and the sensor capacitance linearly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…They monitored the changes during the cell cycle and could distinguish the different cell status [9]. Several groups exploited the dielectrophoretic response of various cells for characterisation and separation purposes [17][18][19][20][21][22][23]. Jones et al reported that E. coli of different serotypes could be discriminated by their dielectric response [19].…”
Section: Introductionmentioning
confidence: 99%
“…They monitored the changes during the cell cycle and could distinguish the different cell status [9]. Several groups exploited the dielectrophoretic response of various cells for characterisation and separation purposes [17][18][19][20][21][22][23]. Jones et al reported that E. coli of different serotypes could be discriminated by their dielectric response [19].…”
Section: Introductionmentioning
confidence: 99%
“…Of the various LOC devices which have followed many are based on electrical methods, including electrophoresis (EP) [3,4] electrowetting on dielectric (EWOD) [5,6] and electrokinetics effects (including dielectrophoresis (DEP) [7][8][9][10] AC electroosmosis (ACEO) [11][12][13][14] and the electrothermal effect [15,16]). These electrical LOCs have found numerous applications in processes such as drug delivery [17][18][19][20][21], cell analysis [22,23], analytical assay [24], and clinical diagnostics [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 2 decades, much effort has focused on resolving this issue by development of sample pretreatment methods that can be integrated with biosensors. These approaches include microfluidic separation (Zuo and others ; Packard and others ; Clime and others ; Kim and others ; Lee and others ; Luka and others ; Gashti and others ), nanoparticle separation (Varshney and Li ; Kwon and others ; Wang and others ), magnetic relaxation switching (Chen and others ), dielectrophoresis (Cheng and others ; Packard and others ; Wang and others ; Yang ; Hamada and others ; Couniot and others ; Kim and others ; Fernandez and others ), immunochromatography (Vyas and others ), acoustofluidic sorting (Li and others ), ferrofluidic manipulation (Kose and others ), or hydrodynamic focusing (Clime and others ). Although not reviewed in detail here, sample pretreatment is a major focus of biosensor research labs and the primary challenges are minimizing destructive sampling, need for pumps, energy, and use of exogenous chemicals.…”
Section: Introductionmentioning
confidence: 99%